1998
DOI: 10.1086/514240
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Interference from Sequential Administration of Live Attenuated Alphavirus Vaccines

Abstract: Two different human vaccine trials examined interference arising from sequential administration of vaccines against heterologous alphaviruses. The first trial indicated that persons previously vaccinated against Venezuelan equine encephalitis virus (VEEV) exhibited poor neutralizing antibody responses to a live attenuated chikungunya virus (CHIKV) vaccine (46% response rate). The second trial prospectively examined neutralizing antibody responses to live attenuated VEEV vaccine in persons previously inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 27 publications
5
61
0
Order By: Relevance
“…7,8 Additionally, human vaccination studies have demonstrated immunological interference from other, related alphaviruses which impede the ability to induce neutralizing antibody production after VEEV vaccination. 7,9 A similar observation of altered ability to produce neutralizing antibody to VEEV has also been made in equines first vaccinated with eastern equine encephalitis virus (EEEV) vaccine or western equine encephalitis virus (WEEV) vaccine. 9 Exploratory attempts have been made to understand the host response mechanisms involved in VEEV immunity and infection.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…7,8 Additionally, human vaccination studies have demonstrated immunological interference from other, related alphaviruses which impede the ability to induce neutralizing antibody production after VEEV vaccination. 7,9 A similar observation of altered ability to produce neutralizing antibody to VEEV has also been made in equines first vaccinated with eastern equine encephalitis virus (EEEV) vaccine or western equine encephalitis virus (WEEV) vaccine. 9 Exploratory attempts have been made to understand the host response mechanisms involved in VEEV immunity and infection.…”
Section: Resultsmentioning
confidence: 69%
“…7,9 A similar observation of altered ability to produce neutralizing antibody to VEEV has also been made in equines first vaccinated with eastern equine encephalitis virus (EEEV) vaccine or western equine encephalitis virus (WEEV) vaccine. 9 Exploratory attempts have been made to understand the host response mechanisms involved in VEEV immunity and infection. Knockout mouse studies for the IFNα/β receptor and for interferon regulatory factors, IRF1 and IRF2 have shown that these animals were susceptible to peripheral infection by virulent or attenuated strains of VEEV.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…18 Reciprocal cross-protection after infection with other alphaviruses occurs in animal models, 19,20 although it is unclear if similar cross protection occurs in humans sequentially exposed to natural infection or live alphavirus vaccines. 21 An isolate from a patient in Thailand, CHIK strain 15561, was used to develop a small lot of vaccine first passaged in green monkey kidney (GMK) cells and then formalin-inactivated before administration to 16 volunteers. 22 The vaccine produced no untoward reactions and was highly immunogenic.…”
Section: Introductionmentioning
confidence: 99%
“…If high doses for multiple immunizations are required, manufacturing of sufficient VRP may be an issue although it should be noted that vaccines using VRP for other diseases are currently in clinical trials [84]. Finally, VEE is also considered a biodefense threat and armed forces and first responders may be vaccinated with VEE vaccine; as a result, pre-existing immunity to VEE may reduce the effectiveness of vaccination with VRPbased vaccines as has been seen with VEE vaccines given to personnel receiving vaccines for other alphaviruses [85].…”
Section: Virus-like Replicon Particles (Vrp)mentioning
confidence: 99%